ASSESSING THE EFFECT OF DEXMEDETOMIDINE DOSAGES ON SHORT-TERM COGNITIVE FUNCTION IN GERIATRIC PATIENTS UNDERGOING HEAD AND NECK CANCER SURGERY: A CROSS-SECTIONAL STUDY. - Dhiraj, Shashank; Kumari, Puja; Kumari, Ritu (Student's Journal of Health Research Africa, 2024)
Background. Geriatric patients undergoing head and neck cancer surgery often face cognitive challenges postoperatively. The study aims to evaluate the impact of varying dosages of Dexmedetomidine (DEX) on short-term cognitive function in this vulnerable population. Methods. A prospective study was carried out, and patients were divided into two groups based on DEX infusion rates. Inclusion criteria encompassed specified surgical regions, while exclusion criteria ensured study population homogeneity. Data on demographics, medical history, surgical details, and DEX infusion were collected. Short-term cognitive function was assessed using the Mini-Mental State Examination (MMSE) on postoperative Day 2. Results. Ninety participants were enrolled, with Group A (lower DEX rates, n=40) and Group B (higher DEX rates, n=50). Baseline characteristics were similar between groups. Mean MMSE scores were considerably higher in Group A (27.5, 95% CI: 26.8-28.2) compared to Group B (26.0, 95% CI: 25.3-26.7) (p < 0.05). The incidence of postoperative delirium was lower in Group A (10%) than in Group B (20%) (p = 0.12). Hemodynamic stability and pain scores were similar between groups. Conclusion. Lower DEX infusion rates were associated with better short-term cognitive function in geriatric patients undertaking head and neck cancer surgery. However, further research is needed to validate these findings and explore potential mechanisms underlying cognitive effects. Recommendations. Based on these findings, clinicians may consider adjusting DEX infusion rates to optimize cognitive outcomes in geriatric patients undergoing similar surgical procedures.